Immunostimulant Activity of Gracilaria sp. and Padina sp. on Immune System of Vannamei Shrimp (Litopenaeus vannamei) Against Vibrio harveyi - Yuni Kilawati; R Adharyan Islamy (Journal of Aquaculture and Fish Health, 2021)
The pathogenic bacterial infection is one of the problems in the cultivation of vannamei shrimp (Litopenaeus vannamei), causing a high mortality rate of cultured shrimp. The use of antibiotics or chemicals with inappropriate concentrations can harm the aquatic environment, cause resistance, and endanger consumer health because the residues from the chemicals used will periodically accumulate in the body of shrimp. One way to control and prevent shrimp disease is to increase the shrimp immune system by using immunostimulants from seaweed. This study aims to analyze the immunostimulant activity of seaweed extract (Gracilaria sp. and Padina sp.) against vannamei shrimp (L. vannamei) infected with Vibrio harveyi by observing the nonspecific immune system based on its hematological features, namely by counting the number of hemocytes and phagocytic activity. The research was conducted at the Hatchery Unit, Brackish Water Cultivation Development Center (BPAP) Situbondo, East Java. Seaweed sample Gracilaria sp. and Padina sp. purchased from seaweed farmers in Jepara, Central Java. The result of this study shows that supplementation of Gracilaria sp. and Padina sp. at a dose of 10 g/kg of feed can increase the total number of hemocytes and phagocytosis activity of L. vannamei shrimp. The best treatment is Gracilaria sp.